Analisis Kesiapan Keterampilan Mahasiswa Tingkat Akhir Jurusan Manajemen Untuk Memasuki Dunia Kerja - Pertiwi, Syarifah Hesty; Linando, Jaya Addin (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study aims to analyze the readiness of final-year Management students' skills in entering the workforce. The research method used is qualitative with a phenomenological approach. The study was conducted by interviewing 15 informants from various universities in Indonesia. The results show variations in students' skills in the categories of technology and interpersonal. Technological skills include digital marketing, Microsoft Office, editing, and SEO, while interpersonal skills involve leadership, good listening, and public speaking. The majority of informants possess technological skills, with some of them holding certifications. Skill development is carried out through formal methods such as courses and internships, as well as informal methods such as learning from social media and sharing with peers. In conclusion, students are aware of the importance of preparing themselves with relevant skills to compete in the ever-changing job market